2014
DOI: 10.5468/ogs.2014.57.4.249
|View full text |Cite
|
Sign up to set email alerts
|

The tryptophan utilization concept in pregnancy

Abstract: The decrease in maternal plasma total (free + albumin-bound) tryptophan (Trp) during the third pregnancy trimester is attributed to induction of indoleamine 2,3-dioxygenase (IDO). When measured, free [Trp] is increased because of albumin depletion and non-esterified fatty acid elevation. The Trp depletion concept in pregnancy is therefore not supported because of incorrect interpretation of changes in Trp disposition and also for not addressing mouse strain differences in Trp-related responses and potential in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 68 publications
(147 reference statements)
2
42
0
Order By: Relevance
“…These results are in line with previous research [26][27][28]. The physiopathological mechanism of decreasing TRP during infection and inflammation is a matter of current discussion [29]. It has been hypothesized early on that diseaseassociated starvation and depletion by microbes may cause these effects.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with previous research [26][27][28]. The physiopathological mechanism of decreasing TRP during infection and inflammation is a matter of current discussion [29]. It has been hypothesized early on that diseaseassociated starvation and depletion by microbes may cause these effects.…”
Section: Discussionsupporting
confidence: 82%
“…A few studies have suggested that the occurrence of postpartum mood symptoms could be related to increased tryptophan breakdown (Figure 1), a physiological phenomenon of pregnancy and the postpartum period (Kohl et al, 2005;Maes et al, 2002). During pregnancy, tryptophan metabolism is altered, with a decrease in total tryptophan and a shift in the proportions of free and bound tryptophan (Badaway, 2014). After pregnancy, both free and bound tryptophan levels gradually return to pre-pregnancy levels (Handley et al, 1977;Schrocksnadel et al, 1996;Schrocksnadel et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Some deleterious effects of elevated KYNA levels during gestation have been reported. The maternal plasma KYNA level is elevated in preeclampsia, and elevated plasma KYNA level during pregnancy was suggested to be strongly associated with increased risk of preeclampsia in women, which is usually accompanied by complications including placental abruption, organ damage, fetal growth restriction and others . Animal studies revealed KYNA was a potent inhibitor of the synthesis of fatty acids in rat liver .…”
Section: Discussionmentioning
confidence: 99%
“…The maternal plasma KYNA level is elevated in preeclampsia, and elevated plasma KYNA level during pregnancy was suggested to be strongly associated with increased risk of preeclampsia in women, which is usually accompanied by complications including placental abruption, organ damage, fetal growth restriction and others. 43,44 Animal studies revealed KYNA was a potent inhibitor of the synthesis of fatty acids in rat liver. 45,46 Elevated levels of KYNA during gestation induced neurochemical, morphological and cognitive deficits in offspring in adulthood, modeling the pathophysiological deficits during the sensitive periods of early development.…”
Section: Variation In Kyna Concentrationmentioning
confidence: 99%